Identification of RAS genotypes that modulate blood pressure change by outdoor temperature - Hong, Yun-Chul; Kim, Ho; Lim, Youn-Hee; Yoon, Hyung-Jin; Kwon, Young-Min; Park, Minseon (Hypertension research, 2013)
The aim of this study was to evaluate the role of polymorphisms of renin-angiotensin system (RAS) genes in modulating outdoor temperature-related blood pressure (BP) responses. Data for RAS gene polymorphisms, BP and outdoor temperature were collected from 4903 subjects from February 2003 to August 2004. Generalized additive and linear models were used to determine whether genetic variants of RAS affected the interplay between outdoor temperature and BP. Outdoor temperature (°C) was inversely associated with systolic BP and diastolic BP. These inverse relationships were stronger in subjects with ACE DD, AGT TT and AGTR1 AA genotypes. In contrast, significant positive temperature-dependent BP responses were found at temperatures above 21.4 °C in subjects with the AGTR1 C allele, but not at temperatures below 21.4 °C. Our findings suggest that subjects with ACE DD, AGT TT or AGTR1 AA genotypes are susceptible to cold temperature-induced BP increase, whereas subjects with AGTR1 C allele have a high risk of BP elevation when exposed to hot temperatures.